The diary of Samuel Pepys - Pepys, Samuel, 1633-1703.; Le Gallienne, Richard, 1866-1947. (New York : Modern Library, 2001)
""The diary which Samuel Pepys kept from January 1660 to May 1669...is one of our greatest historical records and...a major work of English literature," writes the renowned historian Paul Johnson. A witness to the coronation of Charles II, the Great Plague of 1665, and the Great Fire of 1666, Pepys chronicled the events of his day. Originally written in a cryptic shorthand, Pepys's diary provides an astonishingly frank and diverting account of political intrigues and naval, church, and cultural affairs, as well as a quotidian journal of daily life in London during the Restoration."--BOOK JACKET
Keywords: Pepys, Samuel, -- 1633-1703 -- Diaries; Cabinet officers -- Great Britain -- Diaries; Great Britain -- Social life and customs -- 17th century -- Sources; Great Britain -- History -- Charles II, 1660-1685 -- Sources